(untitled) (Global Journal of Human-Social Science, 2021)
Inflation and economic growth have one of the most mysterious relationship in economic theory. The appropriate level of inflation required for economic growth is hard to define. This paper uses annual data from 1961-2019 to investigate the causal relationship between inflation and economic growth in India. Time series data has been collected from International Monetary Fund database. The study uses Vector Error Correction Model and Vector Auto-regression Model identifies the short-run and long-run relationship between inflation and economic development. The study concludes that inflation negatively affects the GDP in the short run but maybe a positive association in the long run. Granger Causality test was also performed to calculate the bidirectional relationship. The examination revealed that that inflation does not granger cause GDP growth. However, it also shows that GDP growth does not cause granger to cause inflation as well.